2004
DOI: 10.1074/jbc.m306850200
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Amino Acid Region Asp695-Tyr698 of Factor V to Procofactor Activation and Factor Va Function

Abstract: There is strong evidence that a functionally important cluster of amino acids is located on the COOH-terminal portion of the heavy chain of factor Va, between amino acid residues 680 and 709. To ascertain the importance of this region for cofactor activity, we have synthesized five overlapping peptides representing this amino acid stretch (10 amino acids each, HC1-HC5) and tested them for inhibition of prothrombinase assembly and function. Two peptides, HC3 (spanning amino acid region 690 -699) and HC4 (contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
78
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(81 citation statements)
references
References 82 publications
2
78
1
Order By: Relevance
“…The C-terminal region of the A2 domain of factor V also contains two acidic sequences within residues 659 -698 (60). A recent study demonstrated that a pentapeptide to an acidic segment comprising factor V residues 695-699 blocked its activation by thrombin (61). That study also demonstrated that mutations within this sequence yielded a factor V molecule that was partially resistant to thrombin-but not factor Xa-catalyzed activation.…”
Section: Discussionmentioning
confidence: 75%
“…The C-terminal region of the A2 domain of factor V also contains two acidic sequences within residues 659 -698 (60). A recent study demonstrated that a pentapeptide to an acidic segment comprising factor V residues 695-699 blocked its activation by thrombin (61). That study also demonstrated that mutations within this sequence yielded a factor V molecule that was partially resistant to thrombin-but not factor Xa-catalyzed activation.…”
Section: Discussionmentioning
confidence: 75%
“…Previous biochemical and mutagenesis data have indicated that the complementary substrate interactive site on factor Va may reside in a hirudin-like sequence within the C-terminal heavy chain of the cofactor involving residues 659 -698 (22)(23)(24). In support of this hypothesis, the recent mutagenesis of the 695 DYDY 698 motif of the factor Va heavy chain dramatically impaired the cofactor function of factor Va in the prothrombinase complex (14). Neither the sequence of the activator nor the cofactor of taipan venom has been determined to understand whether the same substrate interactive site is also conserved in the venom cofactor.…”
Section: Discussionmentioning
confidence: 90%
“…Thus, the charge reversal mutants of proexosite-1 were activated normally by FXa alone, but their activation by the protease in the presence of factor Va was dramatically impaired (13). Further support for a direct interaction between basic residues of proexosite-1 with a complementary site of factor Va was provided by the observation that the mutagenesis of a hirudin-like sequence on the C-terminal heavy chain of factor Va dramatically compromised the cofactor function of factor Va in accelerating the FXa activation of prothrombin by the prothrombinase complex (14).…”
mentioning
confidence: 80%
“…On the basis of extensive investigations, the prothrombin complex is known to consist of phospholipid surface, prothrombin, Ca 2+ and factor Va (FVa). (8)(9)(10)(11)(12) This construct facilitates the activation of prothrombin by ∼3 × 10 5 -fold over catalysis by FXa alone. (13;14) The activation of human prothrombin involves the hydrolysis of two peptide bonds, Arg 322 -Ile 323 followed by Arg 273 -Thr 274 .…”
Section: Introductionmentioning
confidence: 99%
“…(10) Both chains are required for the interaction with FXa, but only the heavy chain binds prothrombin without Ca 2+ . (11) The binding sites for FXa and prothrombin have been located in the middle section (11) and the COOH terminus (12) of the heavy chain of FVa, respectively. (15) In fact, an exosite of FXa, which is exposed upon interaction with FVa for prothrombin tethering, seems to contain amino acids near the active site of the enzyme.…”
mentioning
confidence: 99%